Discursive representations of cities in northeast Germany - Brandt, Julius; Tamásy, Christine (DIE ERDE – Journal of the Geographical Society of Berlin, 2021)
Discursive representations are some of the most important ascriptions for cities and regions in the neo-liberal competition for inhabitants, tourists and companies. This holds especially true for shrinking regions since they feel the pressure of interregional and international rivalry particularly strongly. These representations are formed through language and actions. By analyzing three German cities – Rostock, Stralsund, Greifswald – this paper explores the role of print media in the production of discursive representations in an urban context. Through the methodologic approach of a lexicometric discourse analysis nearly 2000 articles spanning the years 2009 to 2018 were taken from the Süddeutsche Tageszeitung (SZ) and the Frankfurter Allgemeine Zeitung (FAZ), two of Germany’s biggest and most read national daily newspapers, and were analyzed. While the media coverage of Rostock and Greifswald seem to attest a strong and dynamic position that seems to neglect the stigmata attached to shrinking cities and regions, Stralsund seems to play a minor role and might really be caught up in a shrinking discourse.